Analisis Tingkat Kesukaran Soal Ujian Tengah Semester Genap Seni Budaya Kelas X Di SMA Negeri 1 Kecamatan Guguak Kabupaten Lima Puluh Kota - Siti Yulia Amona; Yos Sudarman (SENDRATASIK UNP, 2022)
This study aims to describe the quality of the questions according to the level of difficulty in the even mid-semester examinations for class X Arts and Culture at SMAN 1, Guguak Lima Puluh Kota District. This type of research is descriptive quantitative research. Subjects in the study were taken as many as 50 student answer sheets. In this study, the results of the analysis of the difficulty level of the even mid-semester test for class X Arts and Culture, Guguak 1 District, which consisted of 11 questions were questions number 2, 8, 11, 12, 13, 20, 24, 27, 28, 30, 33, with a percentage 27.5% is expressed by the difficulty index. While 29 questions on numbers 1, 3, 4, 5, 6, 7, 9, 10, 14, 15, 16, 17, 18, 19, 21, 22, 23, 25, 26, 29, 31, 32, 34 , 35, 36, 37, 38, 39, 40, with a percentage of 72.5%. And it was concluded that the difficulty level of the mid-semester test of class X Arts and Culture of SMA Negeri 1 Guguak was not of good quality.